Analysis on Analytical Exposition Text Written by Eleventh Graders of SMA Hang Tuah 4 Surabaya (RETAIN, 2018)
Abstrak Bahasa Inggris merupakan satu dari beberapa subjek penting yang harus dikuasai dalam pendidikan di Indonesia, baik terucap maupun tertulis. Analytical exposition text adalah salah satu tipe teks yang dipelajari di Sekolah Menengah Atas. Analytical exposition text seringkali salah dianggap sebagai hortatory exposition text. Berdasarkan ini, penulis memutuskan untuk mengadakan penelitian ini, yang mana memiliki dua pertanyaan ilmiah, yaitu, bagaimana siswa kelas 11 SMA Hang Tuah 4 membuat analytical exposition text berdasarkan generic structure, dan bagaimana siswa kelas 11 SMA Hang Tuah 4 membuat analytical exposition text berdasarkan language features dari teks tersebut. Peneliti menggunakan metode penelitian deskriptif kualitatif. Penelitian ini berfokus kepada komposisi teks analytical exposition yang dibuat oleh siswa kelas XI IPS 2 dari SMA Hang Tuah 4 Surabaya. Peneliti menganalisa data yang sudah diperoleh dalam bentuk kata-kata dan kalimat. Hasil dari analisis data menunjukkan bahwa kebanyakan dari para siswa memiliki pemahaman yang tidak konsisten terhadap generic structure dan language features dari teks analytical exposition. Kata Kunci: Teks Analytical Exposition, Generic Structure, Language Features. Abstract English is one of the important subjects in Indonesian education system that has to be mastered in either spoken or written. Analytical exposition text is one of several text types that are introduced to the second year of Senior High School. Analytical exposition text is often misinterpreted as hortatory exposition text. Considering this, the writer decided to conduct this analysis study, which has two research questions, how do the eleventh graders of SMA Hang Tuah 4 organize their analytical exposition writing text in terms of its generic structure and how do the eleventh graders of SMA Hang Tuah 4 organize their analytical exposition writing text in terms of its language features?. The researcher uses descriptive qualitative research as the research design. This study concerns on analytical exposition text compositions, which are written by XI IPS 2 class of Sekolah Menengah Atas ( SMA ) Hang Tuah 4 Surabaya. The researcher analyzes the data in the form of words or sentences. The result of data analysis showed that most of the students are having inconsistent understanding about generic structure and language features of analytical exposition. Keywords: Analytical Exposition Text, Generic Structure, Language Features.